Consecutive analysis of mutation spectrum in the dystrophin gene of 507 Korean boys with Duchenne/Becker muscular dystrophy in a single center. Issue 5 (20th January 2017) - Cho, Anna; Seong, Moon‐Woo; Lim, Byung Chan; Lee, Hwa Jeen; Byeon, Jung Hye; Kim, Seung Soo; Kim, Soo Yeon; Choi, Sun Ah; Wong, Ai‐lynn; Lee, Jeongho; Kim, Jon Soo; Ryu, Hye Won; et al.
ABSTRACT: Introduction: Duchenne and Becker muscular dystrophies (DMD and BMD) are allelic X‐linked recessive muscle diseases caused by mutations in the large and complex dystrophin gene. Methods: We analyzed the dystrophin gene in 507 Korean DMD/BMD patients by multiple ligation‐dependent probe amplification and direct sequencing. Results: Overall, 117 different deletions, 48 duplications, and 90 pathogenic sequence variations, including 30 novel variations, were identified. Deletions and duplications accounted for 65.4% and 13.3% of Korean dystrophinopathy, respectively, suggesting that the incidence of large rearrangements in dystrophin is similar among different ethnic groups. We also detected sequence variations in >100 probands. The small variations were dispersed across the whole gene, and 12.3% were nonsense mutations. Conclusions: Precise genetic characterization in patients with DMD/BMD is timely and important for implementing nationwide registration systems and future molecular therapeutic trials in Korea and globally. Muscle Nerve 55: 727–734, 2017